Integrated modalities search framework for digital english language text Holy Qur’an and Tafsir - Qushem, Umar; Zeki, Akram M.; Abubakar, Adamu (The Universal Academy of Science and Technology (UniTech), 2017)
English text is commonly used online for English language and other languages as well. This is one of its attributes that makes its usage gains more popularity than others. English text version of Holy Qur’an and Tafsir can be readable by those who cannot read the Arabic version in the transliterated form. However, a non-Arab native recitation might be different from the Arab native. Nevertheless, both Arab and non-Arab require the knowledge of Tafsir for understanding Qurán word-by-word and its applications. Due to the availability of transliterated English text version of Qurán, it is possible to further utilize the Text processing aspect of generic online search engine architecture to further deliver the knowledge of Qurán. This research uses qualitative explorative approaches to present a framework through which “meaning”, “teaching”, “civilization”, “scientific miracles” and “Aqidah and Ibadah” are integrated for any English transliterated term of Qurán into English explanation source through the knowledge of Tafsir. As a result, online user’s query will extract desirable sequences of refined integration of Quran explanation inculcating knowledge composition of Holy Qur’an and Tafsir. Three short surahs of Holy Qur’an and Tafsir are used for the evaluation of the proposed framework. Text processing procedure is applied and a corpus of the English transliterated terms explanation by Tafsir of Holy Qur’an and Tafsir are generated. This framework is suitable for the design of search engine suitable for spreading the knowledge of Holy Qur’an and Tafsir